Parc#: parallel computing with c# in .net - Ferreira, João Fernando (2005)
This paper describes experiments with the development of a parallel computing platform on top of a compatible C# implementation: the Mono project. This implementation has the advantage of running on both Windows and UNIX platforms and has reached a stable state. This paper presents performance results obtained and compares these results with implementations in Java/RMI. The results show that the Mono network performance, critical for parallel applications, has greatly improved in recent releases, that it is superior to the Java RMI and is close to the performance of the new Java nio package. The Mono virtual machine is not yet so highly tuned as the Sun JVM and Thread scheduling needs to be improved. Overall, this platform is a new alternative to explore in the future for parallel computing